Edukasi Pengelolaan Media Sosial untuk Mengurangi Hoax dan Bullying bagi Siswa Sekolah Menengah Pertama - Melati Budi Srikandi; Chontina Siahaan; Jonathan Jacob Paul Latupeirissa; Ni Komang Vira Yunita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
This activity was carried out to educate junior high school students, in this case, students of public junior high school 3 Marga, Gianyar Regency about proper social media management for students of SMPN 3 Marga in order to reduce hoaxes and bullying. In this activity, material was presented as well as examples of using social media for positive activities, especially how students of SMPN 3 Marga carried out self-actualization through social media and how they contributed to reducing hoaxes and bullying in their surroundings, especially in Pinge Village. Clan, Tabanan. Thus, students of SMPN 3 Marga can use social media to study through accounts that upload subject content, as well as utilize social media as a medium for self-actualization and focus on constructive online activities rather than activities that lead to bullying and hoaxes. Keywords: Education; Social Media Usage; Hoax; Bullying